Оцінка локального ринку ремонтно-будівельних робіт на основі аналізу стану житлового фонду та проектів його реконструкції - Максимова, М. О.; Ніколаєва, Т. В. (Ways to Improve Construction Efficiency, 2012)
On the basis of operation time, physical condition and reconstruction projects of homes the potential market of reparation and construction work for contractors is estimated.